The Spatiotemporal Pattern of Glis3 Expression Indicates a Regulatory Function in Bipotent and Endocrine Progenitors during Early Pancreatic Development and in Beta, PP and Ductal Cells. - Hong Soon Kang; Yukimasa Takeda; Kilsoo Jeon; Anton M Jetten (PLoS ONE)
The transcription factor Glis-similar 3 (Glis3) has been implicated in the development of neonatal, type 1 and type 2 diabetes. In this study, we examined the spatiotemporal expression of Glis3 protein during embryonic and neonatal pancreas development as well as its function in PP cells. To obtain greater insights into the functions of Glis3 in pancreas development, we examined the spatiotemporal expression of Glis3 protein in a knockin mouse strain expressing a Glis3-EGFP fusion protein. Immunohistochemistry showed that Glis3-EGFP was not detectable during early pancreatic development (E11.5 and E12.5) and at E13.5 and 15.5 was not expressed in Ptf1a+ cells in the tip domains indicating that Glis3 is not expressed in multipotent pancreatic progenitors. Glis3 was first detectable at E13.5 in the nucleus of bipotent progenitors in the trunk domains, where it co-localized with Sox9, Hnf6, and Pdx1. It remained expressed in preductal and Ngn3+ endocrine progenitors and at later stages becomes restricted to the nucleus of pancreatic beta and PP cells as well as ductal cells. Glis3-deficiency greatly reduced, whereas exogenous Glis3, induced Ppy expression, as reported for insulin. Collectively, our study demonstrates that Glis3 protein exhibits a temporal and cell type-specific pattern of expression during embryonic and neonatal pancreas development that is consistent with a regulatory role for Glis3 in promoting endocrine progenitor generation, regulating insulin and Ppy expression in beta and PP cells, respectively, and duct morphogenesis.